Spores Setting of Gracilaria gigas (Rhodophyta ,Gracilariales) in Different Artificial Substrates - Irwani Irwani (Universitas Diponegoro, 2013)
The successful of spores settlement on the surface depend on the material and roughed of the surface. The aim of the present study was to find out artificial substrates as spores sticking to be thallus. Randomised design with 4 treatment (raffia line, nylon line, palm line and cotton line) and 9 replicate was used in this study. The highest thallus of G. gigas after grow after 2 moths rearing in the aquarium with the greatest number of thallus which stick on raffia line and the lowest stick on cotton and palm line. The effect of different artificial substrates showed was different significantly (p<0.001). Key Words :Gracilaria gigas, spores, subtrate, raffia line